Cross-Modal Plasticity in Higher-Order Auditory Cortex of Congenitally Deaf Cats Does Not Limit Auditory Responsiveness to Cochlear Implants - Land, Rüdiger (J Neurosci, 2016)
Congenital sensory deprivation can lead to reorganization of the deprived cortical regions by another sensory system. Such cross-modal reorganization may either compete with or complement the “original“ inputs to the deprived area after sensory restoration and can thus be either adverse or beneficial for sensory restoration. In congenital deafness, a previous inactivation study documented that supranormal visual behavior was mediated by higher-order auditory fields in congenitally deaf cats (CDCs). However, both the auditory responsiveness of “deaf” higher-order fields and interactions between the reorganized and the original sensory input remain unknown. Here, we studied a higher-order auditory field responsible for the supranormal visual function in CDCs, the auditory dorsal zone (DZ). Hearing cats and visual cortical areas served as a control. Using mapping with microelectrode arrays, we demonstrate spatially scattered visual (cross-modal) responsiveness in the DZ, but show that this did not interfere substantially with robust auditory responsiveness elicited through cochlear implants. Visually responsive and auditory-responsive neurons in the deaf auditory cortex formed two distinct populations that did not show bimodal interactions. Therefore, cross-modal plasticity in the deaf higher-order auditory cortex had limited effects on auditory inputs. The moderate number of scattered cross-modally responsive neurons could be the consequence of exuberant connections formed during development that were not pruned postnatally in deaf cats. Although juvenile brain circuits are modified extensively by experience, the main driving input to the cross-modally (visually) reorganized higher-order auditory cortex remained auditory in congenital deafness. SIGNIFICANCE STATEMENT In a common view, the “unused” auditory cortex of deaf individuals is reorganized to a compensatory sensory function during development. According to this view, cross-modal plasticity takes over the unused cortex and reassigns it to the remaining senses. Therefore, cross-modal plasticity might conflict with restoration of auditory function with cochlear implants. It is unclear whether the cross-modally reorganized auditory areas lose auditory responsiveness. We show that the presence of cross-modal plasticity in a higher-order auditory area does not reduce auditory responsiveness of that area. Visual reorganization was moderate, spatially scattered and there were no interactions between cross-modally reorganized visual and auditory inputs. These results indicate that cross-modal reorganization is less detrimental for neurosensory restoration than previously thought.